Peningkatan Keterampilan Berbicara Siswa Melalui Model Pembelajaran SQ3R pada Pembelajaran Bahasa - Yuli Astuti; Siti Masrungah; Khusnul khotimah; Siti Fatkhurohmah; M Syabani S; Hasim Asngari (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
Speaking is one of the important language skills in everyday life. One of the learning models that can improve these skills is SQ3R. This research aims to describe the steps, advantages, and disadvantages of SQ3R model implementation in language learning at Madrasah Aliyah Negeri 2 Rembang and Madrasah Aliyah Negeri 1 Kebumen. The research method used a qualitative approach with the research subjects being language teachers. Data were collected through interviews, observations, and documentation. The results showed that the steps of SQ3R include: Survey, the teacher helps students examine the structure of the reading text; Question, the teacher gives directions to formulate clear and relevant questions; Read, students read actively to find answers; Recite, students restate answers without looking at notes; and Review, students review questions and answers. The advantages of this model are that it can arouse curiosity, increase motivation, encourage critical thinking, and help remember material longer. However, the weakness lies in the lack of accuracy and student activeness which can hinder understanding of the material. The study concluded that the SQ3R model is effective in improving students' speaking skills in language subjects.